Quality of life in patients with anogenital warts: A cross‐sectional study using the Dermatology Life Quality Index questionnaire - GC Sagar; Sushil Paudel; Prajwal Pudasaini; Sadiksha Adhikari (Wiley, 2024)
Abstract Background Anogenital warts are Sexually Transmitted Diseases (STDs) caused predominantly by Human Papilloma Viruses (HPV) serotypes 6 and 11. These are one of the commonest causes of STDS, presenting to the Venereology Out Patient Department (OPD)in Nepal. Occurrence of Anogenital warts can affect sexual health of patient and subsequently cause significant embarrassment and impairment in Quality of Life (QoL). Objectives In this study we plan to assess the demographic data of anogenital warts and its impact in Nepalese patients, using a Nepali version of generic Dermatology Life Quality Index (DLQI) questionnaire. Methods All consenting patients with anogenital warts presenting to our OPD from December 2022 to December 2023 were enrolled in this observational study. Clinical evaluation for anogenital warts, sites involved and patient demographics were recorded. All participants were asked to complete the Nepali Dermatology Life Quality Index (DLQI) questionnaire. Results A total of 59 patients were included in this study, of which 71.2 % were males and 28.8% were females. The DLQI score of 10.15 ± 5.09 indicated that genital warts caused a very significant impact on the quality of life of patients. This impact was higher in females as compared to males and in those with shorter duration of disease. Younger patients had a greater impairment in QoL in our study as evidenced by higher DLQI scores. Conclusions Patients with anogenital warts have a significant impact on QoL.